2020
DOI: 10.1002/da.23131
|View full text |Cite
|
Sign up to set email alerts
|

Does continuous positive airways pressure treatment improve clinical depression in obstructive sleep apnea? A randomized wait‐list controlled study

Abstract: Background: Obstructive sleep apnea (OSA) is a highly prevalent sleep disorder that is associated with a range of adverse daytime sequelae, including significantly higher rates of clinical depression than is seen in the general community. Improvements in depressive symptoms occur after treatment of the primary sleep disorder, suggesting that comorbid depression might be an intrinsic feature of OSA. However, there are limited data on whether treatment for OSA in patients diagnosed with clinical depression impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Sixty-three RCTs (74 articles) comparing positive airway pressure with sham positive airway pressure (29 RCTs, 33 articles) or another inactive control (34 RCTs, 41 articles) reported at least 1 eligible health outcome. Most trials identified participants from sleep clinics or referrals, and none focused on persons who were screen detected in primary care settings.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-three RCTs (74 articles) comparing positive airway pressure with sham positive airway pressure (29 RCTs, 33 articles) or another inactive control (34 RCTs, 41 articles) reported at least 1 eligible health outcome. Most trials identified participants from sleep clinics or referrals, and none focused on persons who were screen detected in primary care settings.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, individuals with REM-related OSA displayed worse depression and total mood disturbance subscale scores on the Profile of Mood Scale than individuals without OSA or even combined non-REM and REM OSA ( 10 ). Several randomized clinical trials of OSA treatment with positive airway pressure have demonstrated improvement in depression and anxiety scores ( 11 ), including the very large Sleep and Vascular Endpoints (SAVE) trial, despite only 3.3 average hours of positive airway pressure adherence in those randomized to positive airway pressure ( 12 ). However, most studies have evaluated treatment-associated mood changes in subjects with OSA, but not specifically in individuals with OSA and comorbid psychiatric disease.…”
mentioning
confidence: 99%
“…Clinically interesting points in the treatment of the two conditions include the following: Several studies found that treating OSA patients with comorbid depression with CPAP can improve mood, cognitive and insomnia symptoms. [ 26 29 ] Effective treatment of depression may improve acceptance of OSA treatment and increase motivation to treatment, such as adherence to CPAP use. Using sedative or hypnotic agents, especially benzodiazepines, to aid sleep or reduce anxiety, can worsen OSA symptoms due to muscle relaxation and respiratory depression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that treating OSA patients with comorbid depression with CPAP can improve mood, cognitive and insomnia symptoms. [ 26 29 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation